(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Real symptoms frequently appear even when there is no actual illness. Somatization is the term for when psychic factors are to blame for the symptoms. Real symptoms frequently appear even when there is no actual illness. Somatization is the term for when psychic factors are to blame for the symptoms. Real symptoms frequently appear even when there is no actual illness. Somatization is the term for when psychic factors are to blame for the symptoms. An assessment by a psychiatrist is required to rule out concurrent psychiatric condition. Unaware doctors or surgeons may conduct investigations or diagnostic procedures that could have iatrogenic effects as a result of their ignorance of this sickness. It also puts a significant financial strain on the healthcare system. Many studies have been conducted to identify the best way to treat the condition. Treatment options include psychological and pharmaceutical therapies. In around half of these individuals, MUS resolve on their own within a year. Pharmaceutical therapy includes the use of sedative drugs such benzodiazepines, hypnotics, and antidepressants.